Level of knowledge toward organic rice of farmers in Kelantan / Nurul Imanina Kamal Bahri - Kamal Bahri, Nurul Imanina (Faculty of Plantation and Agrotechnology, 2016)
Agriculture is one of the major contributors to the pollution to Earth from planting until processing. Although the pollution cannot be fully eliminated but the effort to minimize it is a good approach. The goal in agriculture now and for the future is to achieve sustainable agriculture as a result from the imbalance ecosystem and environment. Sustainability in agriculture refers to farmer's being a commercially good competitor in the rapid fluctuating environment to maintain sustainable yield while preserving natural environment, promoting social development and creating economic opportunities (Ismail, 2006 as cited by Othman & Muhammad, 2012). Therefore, organic rice farming is a solution for preserving the environment due to the zero usage of artificial chemicals. The survey involved 10 farmers that had implemented the organic rice cultivation in Kelantan. Data were collected through the distribution questionnaire to the farmers. The findings of this survey are the level of their knowledge about the benefit of organic rice cultivation and to identify willingness of farmers to cultivate organic rice based on their knowledge.